Contemporary Challenges in the Integration of Artificial Intelligence within China’s Higher Education System - Xiao Jingyu; Anna A. Arinushkina; Olga A. Mashkina (Вестник Московского Университета. Серия 20: Педагогическое образование)
Background. The systemic integration of artificial intelligence across various levels of educational system, including higher education, within regional, local, and national educational projects underscores the necessity of developing and testing methodologies for AI implementation, selecting appropriate evaluation methods, and researching best practices for effective deployment and resource support.